QUANTITATIVE AND QUALITATIVE SCREENING OF THE TRADITIONAL PLUM JAM FROM ROMANIA - Ioana TOMA; Mariana PIPIRIGEANU; Florentina Marin HADDAD; Cristina GARLEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Traditional foods are a special category of products that, besides the intrinsic value of preserving and continuing regional and national customs in today's context, must meet consumer demands, particularly in terms of food safety and nutritional value. Increasing the production of this category of food under these conditions becomes a problem for producers, especially small ones. In this context we chose the case study for the identification of the main economic operators and of the fruit-growing areas in Romania, favoring the obtaining of raw materials with special qualities in order to process them. The production of plum jam, the process of obtaining jams traditional products, the quality of the final products and their main features have been analyzed in this research article. The conclusion was that processing and certification as a traditional "plum jam-magiun" product meets consumer safety and security requirements.